KEKUATAN KEPATUHAN WAJIB PAJAK PADA KANTOR SAMSAT KABUPATEN BADUNG - Ni Luh Putu Widhiastuti; Ni Putu Rina Apriyandini; Ni Luh Gde Novitasari (KRISNA: Kumpulan Riset Akuntansi, 2026)
Taxes are contributions made by the people to the state treasury based on law, enforceable without receiving any direct tangible benefits in return, and are used to cover general expenses. Taxpayer compliance reflects tax revenue through periodic and annual tax payments and reporting. Taxpayer compliance demonstrates adherence and awareness of tax compliance. The purpose of this study was to determine the effect of taxpayer awareness, tax rates, tax sanctions, and tax socialization on taxpayer compliance. The purpose of this study was to determine whether the drive-thru system moderated the influence of taxpayer awareness, tax rates, tax sanctions, and tax socialization on taxpayer compliance at the Badung Regency Samsat Office. This study analyzed the effect of taxpayer awareness, tax rates, tax sanctions, and tax socialization on motor vehicle taxpayer compliance, with the drive-thru system acting as a moderator at the Badung Regency Samsat Office. Using moderated regression analysis, data were collected via questionnaire from 100 motor vehicle taxpayer respondents (accidental sampling). The analysis technique used was moderated regression, analyzed using SPSS. The results showed that taxpayer awareness, tax rates, tax sanctions, and socialization had a significant positive effect on taxpayer compliance. The drive-thru system strengthens tax rates, sanctions, and socialization, but does not moderate taxpayer awareness. The model explains 68.2% of the variation in compliance.